Electrical transport in thin films of glassy Ge₄₀Te₆₀-xSbx alloys - Shukla, S.; Kumar, S. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2010)
Glassy alloys of Ge₄₀Te₆₀-xSbx (where x = 2, 4, 6 and 10) were prepared by
conventional rapid melt-quenching technique. The nature of the alloys was ascertained
through X-ray diffraction pattern of the samples. Thin films of the aforesaid materials
could be prepared over the glass substrate by thermal evaporation technique. Vacuum
evaporated indium electrodes were used here to perform electrical measurements.
Coplanar structure of thin films was used in this case. The dc electrical conductivity
measurements have been carried out. The dark conductivity, pre-exponential factor and
activation energy have been calculated for various compositions. It has been found that
the dark conductivity and pre-exponential factor increase, while the activation energy
decreases with Sb concentration in Ge₄₀Te₆₀-xSbx system. The results can be reserved
as an evidence for the chalcogenide nature defects in the above material.